The emergence of youth protest music and arts as alternative media in Zimbabwe: a Gramscian analysis - Kabwato, Chris (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
The primary goal of the research is to examine the reasons for the emergence of - hip-hop-based youth protest music and satirical video comedy in Zimbabwe in a context where democratic and media practice has been restricted. The study examines the strategies and platforms that the young urban-based, musicians and cultural activists employ as they contest the meta-narrative of political nationalists who control the public mass media. The study recognises culture as a site of struggle and seeks to tease out the meaning of specific art forms ('conscious' hip-hop music and faux-news satire) in this very specific period of Zimbabwe's history. The study proposes that the rise of these new forms of hip-hop based protest music, poetry and satirical comedy indicate how through the production and circulation of popular culture, ordinary Africans are able to debate pertinent issues that are marginalised by the official media channels. The study thus sees these artists as organic intellectuals who use alternative media to engage with different publics as they seek to counter hegemonic discourses.
Keywords: Protest songs -- Zimbabwe; Protest poetry -- Zimbabwe; Hip-hop -- Political aspects -- Zimbabwe; Radical theater -- Zimbabwe